A novel ubiquitin mark at the N-terminal tail of histone H2As targeted by RNF168 ubiquitin ligase - Gatti, Marco; Pinato, Sabrina; Maspero, Elena; Soffientini, Paolo; Polo, Simona; Penengo, Lorenza (Cell cycle (Georgetown, Tex.), 2012)
Ubiquitination of histones plays a critical role in the regulation of several processes within the nucleus, including maintenance of genome stability and transcriptional regulation. The only known ubiquitination site on histones is represented by a conserved Lys residue located at the C terminus of the protein. Here, we describe a novel ubiquitin mark at the N-terminal tail of histone H2As consisting of two Lys residues at positions 13 and 15 (K13/K15). This "bidentate" site is a target of the DNA damage response (DDR) ubiquitin ligases RNF8 and RNF168. Histone mutants lacking the K13/K15 site impair RNF168- and DNA damage-dependent ubiquitination. Conversely, inactivation of the canonical C-terminal site prevents the constitutive monoubiquitination of histone H2As but does not abolish the ubiquitination induced by RNF168. A ubiquitination-defective mutant is obtained by inactivating both the N- and the C-terminal sites, suggesting that these are unique, non-redundant acceptors of ubiquitination on histone H2As. This unprecedented result implies that RNF168 generates a qualitatively different Ub mark on chromatin.